Mouse polyomavirus infection induces lamin reorganisation - Bruštíková, Kateřina; Ryabchenko, Boris; Žáčková, Sandra; Šroller, Vojtěch; Forstová, Jitka; Horníková, Lenka (The FEBS journal, 2024)
The nuclear lamina is a dense network of intermediate filaments beneath the inner nuclear membrane. Composed of A-type lamins (lamin A/C) and B-type lamins (lamins B1 and B2), the nuclear lamina provides a scaffold for the nuclear envelope and chromatin, thereby maintaining the structural integrity of the nucleus. A-type lamins are also found inside the nucleus where they interact with chromatin and participate in gene regulation. Viruses replicating in the cell nucleus have to overcome the nuclear envelope during the initial phase of infection and during the nuclear egress of viral progeny. Here, we focused on the role of lamins in the replication cycle of a dsDNA virus, mouse polyomavirus. We detected accumulation of the major capsid protein VP1 at the nuclear periphery, defects in nuclear lamina staining and different lamin A/C phosphorylation patterns in the late phase of mouse polyomavirus infection, but the nuclear envelope remained intact. An absence of lamin A/C did not affect the formation of replication complexes but did slow virus propagation. Based on our findings, we propose that the nuclear lamina is a scaffold for replication complex formation and that lamin A/C has a crucial role in the early phases of infection with mouse polyomavirus.
Keywords: lamin typ B; Polyomavirus Infections; viral replication centres; replikace viru; Cell Nucleus; jaderná lamina; Nuclear Lamina; fosforylace; VP1; Polyomavirus; lamin A/C; Tumor Virus Infections; Phosphorylation; lamin B; buněčné jádro; Capsid Proteins; virové plášťové proteiny; Lamin Type B; Animals; polyomavirové infekce; lamin typ A; Virus Replication; infekce onkogenními viry; Nuclear Envelope; zvířata; myši; jaderný obal; Lamin Type A; Mice; mouse polyomavirus